The Influence of Attitude and Work Competence on the Quality of Public Services at the Woha District Office, Bima Regency - Utari Meilista; Jaenab (Yayasan Baru Haji Samsudin, 2024)
This study aims to determine the effect of work attitudes and competencies on service quality at the Woha District Office, Bima Regency. This type of research is referred to as associative research, which aims to determine the relationship between two or more variables. Namely, the influence of work attitudes and competencies on service quality at the Woha District Office, Bima Regency. The withdrawal technique is a saturated sample by taking all employees, totaling 32 respondents at the Woha Sub-district office, Bima Regency. Data collection techniques using a questionnaire (questionnaire) with a Likert scale. Data analysis techniques using validity test, reliability test, classical assumption test and multiple linear regression with SPSS windows 20. The results of this study 1) There is a significant influence between attitudes towards the quality of public services at the Woha sub-district office, Bima district. 2) There is no significant effect between work competence on the quality of public services at the Woha District Office, Bima Regency. 3) There is a significant influence between attitudes and work competence on the quality of public services at the Woha District Office, Bima Regency.